Melanocytic hyperplasia after burn due to electric heating pad burst. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Burns due to electric heating pad burst are frequently reported in newspapers and media, although the medical literature on the topic is scarce (1). Burns are more frequent during the cold months in children, old people, women, and less healthy population; they are favored by an incautious use of the bag – failure to detach the bag from the electric socket – and by a bad manufacture of the same – in the current case the rupture of the bag released a blackish malodorous liquid, the composition of which we were not able to know –. The actual case is peculiar for the presence of brownish papules linked on histological examination to non-specific inflammation and melanocytic hyperplasia. A brownish pigmentation of reticulated appearance due to incontinence of the melanin pigment has also been described in erythema ab igni, due to repeated exposure to infrared radiation, that is not hot enough to cause an acute burn.